5-Lipoxygenase inhibitors: a review of recent patents (2010 – 2012). (July 2013) - Hofmann, Bettina; Steinhilber, Dieter
<x xml:space="preserve">Abstract</x> Introduction: 5-Lipoxygenase (5-LO) is a crucial enzyme of the arachidonic acid (AA) cascade and catalyzes the formation of bioactive leukotrienes (LTs) with the help of FLAP, the 5-LO-activating protein. LTs are inflammatory mediators playing a pathophysiological role in different diseases like asthma, allergic rhinitis as well as cardiovascular diseases and certain types of cancer. With the rising number of indications for anti-LT therapy, 5-LO inhibitor drug development becomes increasingly important. Areas covered: Here, both recent findings regarding the pathophysiological role of 5-LO and the patents claimed for 5-LO inhibitors are discussed. Focusing on direct inhibitors, several patents disclosing FLAP antagonists are also subject of this review. Novel compounds include 1, 5-diarylpyrazoles, indolizines and indoles and several natural product extracts. Expert opinion: Evaluation of the patent activities revealed only quite moderate action. Nevertheless, several auspicious drug-like molecules were disclosed. It seems that in the near future, FLAP inhibitors can be expected to enter the market for the treatment of asthma. With the resolved structure of 5-LO, structure-based drug design is now applicable. Together with the identification of downstream enzyme inhibitors and dual-targeting drugs within the AA cascade, several tools are at hand to cope with 5-LOs increasing pathophysiological roles.